IoT in Healthcare: Benefits, Challenges and Future Scope of Research - Kolay, Srikanta; Hiwarkar, Tryambak (International Journal of Computer Sciences and Engineering, 2026)
he rapid advancement of the Internet of Things (IoT) has sparked a paradigm shift across industries, revolutionizing traditional approaches to data collection, analysis, and utilization. In particular, the integration of IoT technologies within the healthcare domain has ushered in transformative possibilities that hold the potential to enhance patient care, improve clinical outcomes, and optimize healthcare operations. This research paper aims to comprehensively explore the multifaceted landscape of IoT in healthcare, delving into the benefits, challenges, and untapped avenues of future research. The primary objective of this research is to provide a thorough examination of the advantages offered by IoT applications in healthcare, ranging from empowering real-time patient monitoring to enabling predictive analytics for disease management. IoT's seamless amalgamation with healthcare has paved the way for remote patient monitoring, where wearable devices and sensors continuously collect and transmit vital signs, fostering proactive interventions and personalized healthcare. This real- time health tracking not only empowers patients to actively engage in their well-being but also equips healthcare providers with timely data for informed decision-making. Predictive analytics powered by IoT further elevates disease management by utilizing data-driven insights to anticipate outbreaks, detect anomalies, and enhance preventive strategies. The interconnectedness of IoT devices ensures that patient care is finely tuned and tailored, ultimately contributing to improved patient outcomes and an elevated quality of care. Additionally, the marriage of IoT with healthcare operations manifests in optimized hospital efficiency, streamlining inventory management, resource allocation, and energy consumption.